2013
DOI: 10.1016/j.bcp.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid receptors in non-alcoholic fatty liver disease

Abstract: Accumulating data have shown that bile acids are important cell signaling molecules, which may activate several signaling pathways to regulate biological processes. Bile acids are endogenous ligands for the farnesoid X receptor (FXR) and TGR5, a G-protein coupled receptor. Gain- and loss-of-function studies have demonstrated that both FXR and TGR5 play important roles in regulating lipid and carbohydrate metabolism and inflammatory responses. Importantly, activation of FXR or TGR5 lowers hepatic triglyceride l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 73 publications
(146 reference statements)
1
92
0
1
Order By: Relevance
“…The primary bile acid chenodeoxycholic acid serves as the strongest ligand for the farnesoid X receptor (FXR) (108). Bile acid activation of FXR and another bile acid receptor, TGR5, has been shown to decrease hepatic lipid accumulation and inflammation (114). A study in humans found decreased expression of FXR and increased expression of LXR, SREBP-1, and FAS proteins in the liver of patients with NAFLD compared with healthy controls (115).…”
Section: Liver Responses To Dfmentioning
confidence: 99%
“…The primary bile acid chenodeoxycholic acid serves as the strongest ligand for the farnesoid X receptor (FXR) (108). Bile acid activation of FXR and another bile acid receptor, TGR5, has been shown to decrease hepatic lipid accumulation and inflammation (114). A study in humans found decreased expression of FXR and increased expression of LXR, SREBP-1, and FAS proteins in the liver of patients with NAFLD compared with healthy controls (115).…”
Section: Liver Responses To Dfmentioning
confidence: 99%
“…Importantly, activation of farnesoid X receptor/TGR5 lowers intrahepatic triglyceride content and inhibits inflammation. 55 In addition, farnesoid X receptor/TGR5 activation coordinates the immune phenotype of monocytes and macrophages both in vitro and in vivo, 56 and taken together, this evidence suggests that farnesoid X receptor and TGR5 may be both ideal targets for NAFLD treatment.…”
Section: Putative Mechanisms Linking Nafld To Cvdmentioning
confidence: 99%
“…[1][2][3][4] However, recent interest in bile acids over the past few years has shed new light on their roles in both the synthetic and regulatory metabolic pathways, pertaining to lipid, carbohydrate and cholesterol regulation acting as indispensable signalling molecules co-ordinating these network of biological processes. 5 Whilst bile acids (Chenodeoxycholic acid (CDCA), Deoxycholic acid (DCA), Lithocholic acid (LCA), Cholic Acid (CA)) can negatively feedback their own production, 6 they can also act as endogenous ligands for nuclear receptors to facilitate this regulation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Whilst bile acids (Chenodeoxycholic acid (CDCA), Deoxycholic acid (DCA), Lithocholic acid (LCA), Cholic Acid (CA)) can negatively feedback their own production, 6 they can also act as endogenous ligands for nuclear receptors to facilitate this regulation. 3,4,7 The nuclear receptor, Farnesoid X Receptor (FXR; NR1H4) was the first bile acid receptor discovered, In terms of nuclear receptor activation, PXR and VDR are stimulated by lithocholic acid (EC50 of approximately 100 nM), which is a hydrophobic bile acid derived from the 7-dehydroxylation of CDCA by intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation